Pharmacokinetics and Bioavailability Study of a Prednisolone Tablet as a Single Oral Dose in Bangladeshi Healthy Volunteers. Issue 3 (19th July 2018) - Bashar, Tafsir; Apu, Mohd Nazmul Hasan; Mostaid, Md Shaki; Islam, Md Saiful; Hasnat, Abul
The aim of the study was to assess the pharmacokinetic and bioavailability of 2 formulations of 5-mg prednisolone tablets, reference product (Teva UK Limited) and Pred (Eskayef Bangladesh Ltd) as test product. The open-label, randomized, 2-way crossover studies were conducted on 14 healthy subjects. Participants were assigned to receive both products as a single dose (20 mg formulations, 4 × 5 mg tablets) followed by a 2 weeks' washout period. Following oral administration, samples were obtained at various time intervals and analyzed for prednisolone concentrations using a validated high-performance liquid chromatography assay method with ultraviolet detection. The obtained values for test and reference products were 683.00 ± 94.54 ng/mL and 635.16 ± 125.57 ng/mL for Cmax ; 2716.54 ± 196.28 ng·h/mL and 2780.5 ± 119.73 ng·h/mL for AUC0-12 ; 3284.36 ± 138.12 ng·h/mL and 3317.96 ± 133.95 ng·h/mL for AUC0-∞, respectively. From the paired Student t test, no significant differences between 2 formulations were observed ( P > .05). The 90% confidence intervals of Cmax, AUC0-12, and AUC0-∞ were found to be 99.0% to 100.9%, 99.4% to 100.5%, and 99.9% to 101.3%, respectively. Finally, it can be concluded that Pred (Test) of Eskayef Bangladesh Ltd and prednisolone (Reference) of Teva UK Limited are bioequivalent and interchangeable.